PENGARUH MANAJEMEN ASET TERHADAP OPTIMALISASI PEMANFAATAN ASET TETAP PEMERINTAH DAERAH - Umbora, Edwin; Falah, Syaikhul; Pangayow, Bill J. C. (Fakultas Ekonomi, Universitas Cenderawasih, 2018)
This study aims to examine the effect of Asset Management on Fixed Assets Optimization of Local Governments. This research was conducted at the Regional Government of Waropen District. Asset management variables consist of Inventory, Identification, Legal Audit and Asset Assessment. Thirty six (36) employees who have knowledge of asset utilization and regional goods management staff were involved as respondents on this survey. The analytical tool in this study uses SPSS. This type of research is focusing on verification of the effect of independent variables on the dependents, and this research uses Multiple Regression Analysis, so that the result is expected to meet the Classical Assumption Test. The results of this study indicate simultaneously that inventory, identification, legal audit and scoring system of the variables influence the optimization of Fixed Asset Utilization, with a significance value of 0,000. However, partially, inventory and identification have no effect with a greater significance value p value. Meanwhile, the Legal Audit and Assessment affect the Optimization of Fixed Asset Utilization moderately.